A noção filosófico-pedagógica de “caminho” no karate-do de Gichin Funakoshi e suas potencialidades educacionais - Zucchi, Sidinei Luís (2019)
This research constitutes a reflexive-theoretical investigation about the thought of Gichin Funakoshi, the formulator of the modern Karate-Do, with the objective of abstracting to him the philosophical-pedagogical content - contained in the notion of “Do”, “Path” - and of examine its educational potentialities in the teachinglearning of martial art. Present in formal and non-formal educational spaces, it was observed that in the region object of research, the North / Northwest of Rio Grande do Sul, the teaching of Karate-Do lacks formal theoretical pedagogical elaboration and is reduced to the physical dimension. and practice technique. Since this reality contrasts with the historical, philosophical, pedagogical, anthropological, religious and ethical richness of the traditional Japanese martial arts universe - the case of Karate-Do -, the paper proposes a reflection that considers the importance of the presence of these other dimensions in the teaching and learning of Martial Art, preserving the richness of its historical construct, especially with regard to its interface with pedagogy, pointing out one possibility among others - that of the recovery of Funakoshi's philosophicalpedagogical thinking - so that it can theoretically be based that teaching. The text also has a propaedeutic character, drawing attention to the importance of joining in doing, thinking practice doing, also based on the scope of these formulations and the principles underlying the work examined, a proposal for pedagogical intervention.